2013
DOI: 10.1111/jicd.12080
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and attitudes towards HIV/AIDS: a survey among dental students in Ajman, UAE

Abstract: Appropriate educational programs may alter the misconceptions and the negative attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…A survey of 119 men and 148 women at the university of Al-Ain state indicated that HIV knowledge was poor among 75% of the respondents (20). A study of 106 dental students in Ajman state indicated that HIV knowledge was poor among 39.5% of the respondents and stigma against HIV was reported (21). Red Crescent Organization has provided some HIV peer education among young people.…”
Section: Resultsmentioning
confidence: 99%
“…A survey of 119 men and 148 women at the university of Al-Ain state indicated that HIV knowledge was poor among 75% of the respondents (20). A study of 106 dental students in Ajman state indicated that HIV knowledge was poor among 39.5% of the respondents and stigma against HIV was reported (21). Red Crescent Organization has provided some HIV peer education among young people.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to findings from other studies in the MENA region, they found misconceptions about modes of transmission and negative attitudes towards people living with HIV, with 75% of students considered to have low knowledge about HIV/AIDS and males were found to have better knowledge compared to females. A more recent study conducted in Ajman (UAE) in 2013 investigated dental student’s knowledge about modes of transmission of HIV/AIDS and their attitudes towards patients being treated [ 13 ]. Results also showed that students’ overall knowledge score was only 67% and that they had high levels of negative attitudes towards people with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…A study among medical and nursing students in Fiji showed adequate HIV knowledge and favorable attitudes towards HIV patients [16]. Similar results were reported among dental students in the United Arab Emirates [17]. However, a survey among pre-clinical students in Israel found that although their knowledge was relatively good, prejudicial attitudes remained prevalent, which was attributed to shame-related stigma and fear of contagions [18].…”
Section: Introductionmentioning
confidence: 59%